Analisis Pertumbuhan Ekonomi dan Ketimpangan Pendapatan Antar Kecamatan di Kabupaten Gianyar - Eka Raswita, Ngakan Putu Mahesa; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 3, Maret 2013 (pp. 119-172), 2013)
This study aims to analyze economic growth and income disparities among districts in Gianyar regrency. This research used secondary data have been applied Klassen Typology, Williamson Index and Regresion methods. Klassen typology analysis result that Gianyar regency in divided in to four classifications of growth: rapid growth region, retarted region, growing region, relatively backward region. According to williamson index disparity income in Gianyar regency generally increased from the period 1993 until 2009. Although still relatively low increases limp average value of 0,300 (stil below 0,5). Kuznets hypothesis showing the relationship between economic growth and inequality inverse U-Shaped effect in Gianyar This researchis recommended to the local goverments implemanted and take more attention to the low growth and low income districts without neglecting areas that have been developed and equality of results  outcomes of development
Keywords: Kuznets hypothesis; Disparity; Economic growth